2020
DOI: 10.1186/s12905-019-0871-6
|View full text |Cite
|
Sign up to set email alerts
|

Work-family balance and the subjective well-being of rural women in Sichuan, China

Abstract: BackgroundDue to the great burden of family and the conflicts among family, society and career roles resulting from migrant working, rural women suffer more conflicts between work and family and need more social attention. Previous studies of the conflicts between family and work mainly focus on the group of career women, and there is a lack of the research on the conflicts between work and family of rural women, which needs to be systematically and further studied.MethodsThis study used a sample survey of 380… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
63
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(73 citation statements)
references
References 19 publications
8
63
2
Order By: Relevance
“…However, stratification of the association between the two phenomena by country showed that significant associations between IPV and pregnancy termination among AGYW existed in Benin, Burkina Faso, Cote D'lvoire, Gambia and Mali (West Africa); Comoros, Rwanda and Uganda (East Africa); Chad, Congo DR and Gabon (Central Africa); and Malawi and Zambia (Southern Africa). Similar findings have been observed in other specific countries within the sub-region such as Cameroon ( Alio et al, 2011 ), Ethiopia ( Tiruye et al, 2020 ), Ghana ( Tenkorang, 2019 ), Nigeria ( Bola, 2016 ) and Tanzania ( Stöckl et al, 2012 ) in confirmation of the significant association between IPV and pregnancy termination in SSA. Beyond SSA, other studies have also found a positive association between IPV and pregnancy termination ( Afiaz, Biswas, Shamma, & Ananna, 2020 ; Devries et al, 2010 ; Khan, Dongarwar, Aliyu, & Salihu, 2019 ; Rahman, 2015 ).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…However, stratification of the association between the two phenomena by country showed that significant associations between IPV and pregnancy termination among AGYW existed in Benin, Burkina Faso, Cote D'lvoire, Gambia and Mali (West Africa); Comoros, Rwanda and Uganda (East Africa); Chad, Congo DR and Gabon (Central Africa); and Malawi and Zambia (Southern Africa). Similar findings have been observed in other specific countries within the sub-region such as Cameroon ( Alio et al, 2011 ), Ethiopia ( Tiruye et al, 2020 ), Ghana ( Tenkorang, 2019 ), Nigeria ( Bola, 2016 ) and Tanzania ( Stöckl et al, 2012 ) in confirmation of the significant association between IPV and pregnancy termination in SSA. Beyond SSA, other studies have also found a positive association between IPV and pregnancy termination ( Afiaz, Biswas, Shamma, & Ananna, 2020 ; Devries et al, 2010 ; Khan, Dongarwar, Aliyu, & Salihu, 2019 ; Rahman, 2015 ).…”
Section: Discussionsupporting
confidence: 88%
“…Considering the role IPV plays in fetal death, understanding the association between IPV and pregnancy termination, particularly in SSA where pregnancy termination and IPV are very high is essential. However, in SSA, only country-specific studies have been carried out in Cameroon ( Alio et al, 2011 ), Ethiopia ( Tiruye, Chojenta, Harris, Holliday, & Loxton, 2020 ), Ghana ( Tenkorang, 2019 ), Nigeria ( Bola, 2016 ) and Tanzania ( Stöckl, Filippi, Watts, & Mbwambo, 2012 ) on the association between IPV and pregnancy termination. None of these studies specifically focused on AGYW, despite previous studies recording high prevalence of pregnancy termination among this cohort of women ( Leppälahti et al, 2012 ; Onukwugha et al, 2020 ; Sánchez-Páez & Ortega, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…The difference might also be due to larger gaps in the study period between current and previous studies. The current study was also significantly higher than studies conducted in developing countries like Nigeria (63.5%) [ 48 ], Ghana (34.5%) [ 49 ], Kenya (25.3%) [ 50 ], Sudan (11%) [ 51 ], and West Shoa zone, Ethiopia (22.1%) [ 52 ]. This might be due to the fact that despite the early recommendation of WHO, CDC, and FIGO, preconception care is a new concept in many countries.…”
Section: Discussioncontrasting
confidence: 55%
“…Overall information regarding the prevalence of cervical cancer screening service utilization was obtained from various regions of the country. Ten of the studies involved participants from the Amhara region [35][36][37][38][39][40][41][42][43][44], eleven from the Oromia region [45][46][47][48][49][50][51][52][53][54][55], nine from the SNNPR [56][57][58][59][60][61][62][63][64], four from Tigrai [65][66][67][68], eight from Addis Ababa [69][70][71][72][73][74][75][76], one study involving participants from the Amhara, SNNPR and Afar regions [77], and another study involving participants countrywide [25]. Regarding sampling, all of the studies used the probability sampling technique ( Table 1).…”
Section: Plos Onementioning
confidence: 99%